Effects of phonon interference through long range interatomic bonds on thermal interface conductance - Han, Haoxue; Feng, Lei; Xiong, Shiyun; Shiga, Takuma; Shiomi, Junichiro; Volz, Sebastian; Kosevich, Yuriy A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2016)
We investigate the role of two-path destructive phonon interference induced by interatomic bonds beyond the nearest neighbor in the thermal conductance of a silicon-germanium-like metasurface. Controlled by the ratio between the second and first nearest-neighbor harmonic force constants, the thermal conductance across a germanium atomic plane in the silicon lattice exhibits a trend switch induced by the destructive interference of the nearest-neighbor phonon path with a direct path bypassing the defect atoms. We show that bypassing of the heavy isotope impurity is crucial to the realization of the local minimum in the thermal conductance. We high-light the effect of the second phonon path on the distinct behaviors of the dependence of the thermal conductance on the impurity mass ratio. All our conclusions are confirmed both by Green’s Function calculations for the equivalent quasi-1D lattice models and by molecular dynamics simulations.